"The Green Sea Yard of Varna" – the innovative project in the focus of early child development. (30th September 2020) - Valtcheva, E; Dimitrova, T; Moutafova, E; Vladeva-Spasova, S; Ivanova, I; Stefanova, R; Popova, I; Slavova, A; Dimitrova, D; Dokova, K
Abstract: We present an innovative approach to early child development (ECD), designated as a priority for all societies. Traditional ECD services of the Bulgarian health system are predominantly medical or pedagogical provided by GPs and nurseries. This leaves space for interdisciplinary services based on the ideas of Françoise Dolto focused on child-parent relationships. The Green Sea Yard of Varna, Bulgaria, aims at providing accessible space for early socialization of children and preventive psychosocial services by experts in ECD. The process oriented work combines: psychosocial accompaniment, social group & community work, psychoanalytic consultation with medical expertise. Specialists use direct observation, interviews, analysis of available information, hypothesis development. Questions to be answered: is there a recognized need for a space enhancing and stimulating the interaction between the three main subject in ECD child-parents-specialists; is there a need for a transitional space between the home and kindergarten enabling early child socialization; which are the most prevalent mental and behavioral problems and their earliest symptoms. For 104 working days (December 2018-February 2020), 2 000 visits of 257 children have been performed, including 400 individual consultations of 51 children at risk. Smooth adaptation to nursery was experienced by 15, 5% of children. The most prevalent problems are: insufficient to lacking parent-child verbal communication; delayed speech development; aggressive behavior towards peers. The main lessons are: (1) There is a recognized by specialists, families and the community need for transitional spaces enabling children to experience first social encounters and concepts of social rules and norms; (2) the space stimulates both formal and informal quality communication between specialist and parents and mutual informal support between parents; (3) leading to a new view for the child as an autonomous person. Key messages: The Green Sea Yard of Varna is the first innovative space for interdisciplinary approach to ECD, early socialization, care & prevention in our community fully applicable to other places and cultures. The project is in line with SDGs, contemporary scientific visions for the first 1000 days of a child's life and the WHO strategy for the prevention of child's health in the family and in society.